PERBEDAAN DAYA HAMBAT MADN KONSENTRASI 100% TERHADAP PERTUMBUHAN BAKTERI PORPHYROMONAS GINGIVALIS DAN AGGREGATIBACTER ACTINOMYCETEMCOMITANS - Indah Wulandari; Emriadi Emriadi; Kosno Supriyanto (Faculty of Dentistry Universitas Andalas, 2018)
Periodontal disease is the second common oral health disease after dental caries. Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are the main species of bacteria that cause periodontitis. Improper use of antibiotics can cause bacterial resistence to antibiotics. Essential oil from Pogostemon cablin, Benth leaf is an essential oil from herb contains eugenol and terpenoid compounds which can be used as an alternative antimicrobial agent. The purpose of this research was to know the difference of inhibitory effect of Pogostemon cablin, Benth leaf essential oil to Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans.The method of this research was experimental laboratories with posttest only control group design. This Research was done using disc diffusion method on the Mueller Hinton Agar. The inhibition zone around the disc was measured by sliding caliper. The results were analyzed with non parametric test Mann Whitney.The results showed that Pogostemon cablin, Benth leaf essential oil had the inhibition zone. The inhibition zone againts Porphyromonas gingivalis was 13,47 mm and 41,15 mm on Aggregatibacter actinomycetemcomitans. The statistical test showed that Pogostemon cablin, Benth leaf essential oil can inhibit both bacterial growth with the bigger inhibition was on Aggregatibacter actinomycetemcomitans bacteria growth.